USING INTERACTIVE METHODS TO INCREASE STUDENTS’ VOCABULARY IN ENLISH LESSONS (Ustozlar uchun, 2026)
This paper explores the effectiveness of interactive vocabulary instruction in enhancing learners’ communicative competence in English language classrooms. The research is grounded in Communicative Language Teaching, Task-Based Learning, Cognitive Load Theory, and Dual Coding theory. Within the context of Uzbekistan’s educational reforms, developing communicative competence has become a national priority, which requires innovative, learner-centered approaches to vocabulary teaching. A classroom- based action research methodology was applied, involving a series of interactive vocabulary activities such as “ Where are you from?”, “Colorful Plane ”, “ Smart ball”, “Magic snowball” and “ Happy fish”.